EVALUASI PROGRAM PEMBELAJARAN PENDIDIKAN JASMANI DI PONDOK PESANTREN MU’ALIMIN MUHAMADIYA H DAERAH ISTIMEWA YOGYA KARTA - Armin Suhaidin, Lalu (Jurnal Pendidikan Jasmani Indonesia, 2016)
Abstract This research purposed to evaluated the program of physical education learning that was viewed from the components were (1) context (2) input (3) process and (4) the school output. The context component were consists of program and purpose. The input component were consists of syllabus, lesson material, media or tool of learning, teacher, student, infrastructure and the condition of learning environment. The component of process were consists of the readiness of physical education learning, implementation and evaluation. Whereas, the product component was the achievement or student’s value on the physical education learning in pondok pesantren Mu’alimin Muhammadiyah Yogyakarta. This research was study of evaluation by using qualitative analysis and quantitative descriptive was purposed to evaluate the physical education program. The population of study was all students of junior high school (VII and VIII class) and senior high school (X and XI class) of pondok pesantren Mu’alimin Muhammadiyah Yogyakarta which amount 832 students. The sample of research were taken as much as 276 students, consists of 149 students of junior high school and 127 students of senior high school. The data of research was gathered through interview, observation, documentation and questioner, the result of this research founded that the management of physical education learning program, if reviewed from the input form of the availability of the lesson material media, learning media, teacher, infrastructure and the condition of environment, if was viewed from the process in good category. With the average score was 2.60 (1-4 scale) according to student and 3.05 according to teacher was in good category. If was seen from the achievement product or student’s value proved that the physical education was in good category. Key Word: evaluation, context, input, process, product, learning, physical education. Abstrak Penelitian ini bertujuan untuk mengevaluasi program pembelajaran pendidikan jasmani yang ditinjau dari komponenkomponen berikut: (1) konteks, (2) input, (3) proses, dan (4) output sekolah. Komponen konteks terdiri atas program dan tujuan. Komponen iput terdiri atas silabus, materi pelajaran, media atau alat pembelajaran, guru, mahasiswa, infrastruktur dan kondisi lingkungan belajar. Komponen proses terdiri atas kesiapan belajar pendidikan jasmani, pelaksanaan dan evaluasi. Sedangkan, komponen produk adalah prestasi atau nilai siswa pada pembelajaran pendidikan jasmani di Pondok Pesantren Muallimin Muhammadiyah Yogyakarta. Penelitian ini merupakan penelitian evaluasi dengan menggunakan analisis data kualitatif dan deskriptif kuantitatif yang bertujuan untuk mengevaluasi program pendidikan jasmani. Populasi penelitian adalah seluruh siswa sekolah SMP (kelas VII dan VIII) dan SMA (kelas X dan XI) dari Pondok Pesantren Muallimin Muhammadiyah yang berjumlah 832 siswa. Sampel penelitian diambil sebanyak 276 siswa, terdiri atas 149 siswa dari SMP dan 127 siswa SMA. Data penelitian dikumpulkan melalui wawancara, observasi, dokumentasi dan kuesioner, hasil penelitian ini ditemukan bahwa pengelolaan program pembelajaran pendidikan jasmani, jika ditinjau dari input ketersediaan media bahan pelajaran, media pembelajaran, guru, infrastruktur dan kondisi lingkungan, jika dilihat dari proses dikategorikan dalam kategori baik. Dengan skor rata-rata 2.60 (1-4 skala) menurut siswa dan 3.05 menurut guru masuk dalam kategori baik. Jika dilihat dari produk prestasi atau nilai siswa terbukti bahwa pendidikan jasmani masuk dalam kategori baik. Kata kunci: evaluasi, konteks, input, proses, produk, pembelajaran, pendidikan jasmani.